Feminism, matrilinealism, and the `House of Women' in contemporary women's fiction. - Cosslett, Tess (Journal of Gender Studies)
Investigates the ways in which a matrilineal narrative affects the space/time structures of some recent women's fiction. Use of the Bakhtinian concept of chronotope; Structures produced by the intersection of feminism and matrilinealism; Women's fiction investigated.